PHARMACOKINETIC DRUG INTERACTION BETWEEN CLOPIDOGREL AND ESOMEPRAZOLE IN ADULT HEALTHY MALE VOLUNTEERS - K, Bhargav; B, Venkata Subbareddy; K, Venkata Sivakrishna; G, Himaja; Georgep, Samuel Gideon; K, Bhaskar Reddy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Proton pump inhibitors (PPIs) are known to impair cytochrome P2C19 mediated activation of clopidogrel, the antiplatelet agent used for cardiovascular risk prevention. Esomeprazole is an optical isomer of omeprazole with better efficacy and tolerability than conventional PPIs. Esomeprazole is often co-administered with clopidogrel considering the risk of associated gastrointestinal bleeding. This study was designed to determine the effect of esomeprazole on the mean pharmacokinetic profile clopidogrel. Methods: A total of 14 adult healthy male participants who volunteered participation were enrolled, randomized equally into two cross-over sequences, dosed with clopidogrel and clopidogrel + esomeprazole in respective periods. Blood samples were collected through antecubital or forearm vein indwelling catheter. Concentration of clopidogrel parent prodrug in isolated plasma was determined using validated sensitive liquid chromatography – mass spectrometry. Pharmacokinetic modeling was carried out using PKSOLVER add-in for Microsoft Excel. Results: The pharmacokinetic profile of clopidogrel was non-significantly altered by esomeprazole. Statistically significant difference in peak plasma concentration, apparent volume of distribution, and clearance of clopidogrel was observed only during period II in participants co-dosed with esomeprazole (p=0.0483, 0.0011, and 0.0015, respectively). All other primary and secondary pharmacokinetic parameters displayed minor alterations during either period (p>0.05). Conclusion: The non-significant alteration of clopidogrel pharmacokinetics by esomeprazole can be potentiated by underlying predisposing factors such as the presence of CYP2C19 allelic variants and increasing the risk of cardiovascular events. Hence, co-administration of clopidogrel and esomeprazole should be under clinical monitoring and is not recommended in poor responders of antiplatelet therapy with clopidogrel.